Confiança na polícia na América Latina a partir de atitudes políticas e desempenho institucional - Geélison Ferreira da Silva (2022)
The objective of this thesis is to explain the trust in the police in the Latin American region. Two predominant theoretical approaches are explored. The attitudinal considers the effect of political attitudes; and institutional, considers the performance of institutions on the dependent variable, at micro and macro social levels. The need for integration between the two approaches is evident. The hypothesis of the thesis is that, in contexts of low quality of democracy and poor performance of the police, both in terms of effectiveness in guaranteeing public security and respect for the law, it is possible to have institutional trust if citizens' attitudes are authoritarian. In other words, trust may not mean institutional effectiveness or civics. The effects of political attitudes on the dependent variable (trust in the police) are tested using the country fixe d effects model. Likewise, the effects of institutional performance are tested to then analyze the effects of the two sets of variables (attitudinal and institutional) in the same model. Also, effects of interactive terms composed by attitudinal and institutional variables are scrutinized. The results partially confirm the hypotheses and attest that political attitudes and institutional performance are important in explaining peoples´s trust in the police. Specifically, authoritarian attitudes favor it in t he context of Latin America. The interaction between institutional and attitudinal variables demonstrates that poor institutional performance regarding security enhances the association of authoritarian attitudes with reduced trust in police organizations, contradicting the hypothesis. However, the quality of democracy and the "Rule of Law" keep the most democratic individuals away from the positive association between authoritarian attitudes and trust in the police, approaching the proposed hypotheses. The thesis mainly brings three considerably original contributions to the field of study, by integrating culturalist (attitudinal) and institutionalist approaches, identifying a positive association between authoritarianism and institutional trust, and showin g that the quality of democracy and the rule of law work as " antidote” to this association.